The small molecule IMR-1 inhibits the Notch transcriptional activation complex to suppress tumorigenesis - Astudillo, Luisana (Cancer Res, 2016)
In many cancers, aberrant Notch activity has been demonstrated to play a role in the initiation and maintenance of the neoplastic phenotype and in cancer stem cells, which may allude to its additional involvement in metastasis and resistance to therapy. Therefore, Notch is an exceedingly attractive therapeutic target in cancer, but the full range of potential targets within the pathway have been under-explored. To date, there are no small molecule inhibitors that directly target the intracellular Notch pathway or the assembly of the transcriptional activation complex. Here, we describe an in vitro assay that quantitatively measures the assembly of the Notch transcriptional complex on DNA. Integrating this approach with computer-aided drug design, we explored potential ligand binding sites and screened for compounds that could disrupt the assembly of the Notch transcriptional activation complex. We identified a small molecule inhibitor, termed Inhibitor of Mastermind Recruitment-1 (IMR-1), that disrupted the recruitment of Mastermind-like 1 (Maml1) to the Notch transcriptional activation complex on chromatin, thereby attenuating Notch target gene transcription. Furthermore, IMR-1 inhibited the growth of Notch-dependent cell lines and significantly abrogated the growth of patient-derived tumor xenografts. Taken together, our findings suggest that a novel class of Notch inhibitors targeting the transcriptional activation complex may represent a new paradigm for Notch-based anticancer therapeutics, warranting further preclinical characterization.